OBSERVATION ON THE INTESTINAL PARASITIC INFECTIONS - M.Rezaeian (Tehran University of Medical Sciences, 1986)
During 1980-82, a total number of 4143 stool samples, from 2332 males and 1811 females, referred to the Central Laboratory of the School of Public Health, were examined for intestinal parasites. All the specimens were examined for intestinal parasites. All the specimens were examined by formol-ether concentration and wet-mount (ringer solution) techniques. The main prevalent pathogenic parasites were Entamoeba histolytica (8.7%), Giardia lamblia (16.1%), and Hymenolepis nana (3.2%). The overall infection rate with protozoa, metazoan and both were 45%, 18.3% and 53.8% respectively.